Relationship between Workplace Related Violence and Job Satisfaction among Nurses Staff - Duaa Kadhim Sabbar, Wissam Jabbar Kassim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Violence in the workplace is a global public health problem and has caused a serious threat to the physical and mental health of health care workers. Furthermore, workplace violence also has a negative impact on the behavior of health care workers in the workplace. Aims: The purpose of study is to investigate the relationship between workplace related violence and job satisfaction among nurses’ staff. Methods: A descriptive correlational study conducted in Nasiriya Province/ Iraq, by simple random sample of 209 nurses is selected through the use a probability sampling approach. The reliability of the questionnaire was achieved through a pilot study and then presented to experts to prove its validity. The total number of items included in the questionnaire was 30-items for work related violence and 17-tiems for job satisfaction. The data was collected by using the self-report method and analyzed by the application of descriptive and inferential statistical data analysis approach. Results: The results of the study indicated that (50.2%) of the nurses exhibited a moderate workplace related violence and (69.4%) moderate job satisfaction. There were negative significant correlation between workplace related violence and job satisfaction (r= -0.401; p=0.001). Conclusion: Job satisfaction among nurses was found to be inversely connected with workplace violence "high work-related violence reduced job satisfaction". Workplace policies and procedures that focus on environmental security reporting and monitoring, as well as instructional seminars for nurses, are reducing violence and increasing job satisfaction.